Carcinoma of middle ear - Dragoslava Đerić (Биомедицинска истраживања, 2019)
Carcinoma of the middle ear is a rare otologic disease. The development of malignancy is most commonly associated with chronic inflammation of the middle ear, although the mechanisms of this development have not been clarified yet. The symptoms of the carcinoma are not always specific and the cancer is frequently diagnosed in its advanced stage. Early evidence-based diagnosis implies a thorough evaluation and identification of cancer signs and symptoms. If ear discharge is followed by an intensive pain, bleeding from the ear, occurrence of peripheral facial nerve palsy, vertigo and hearing loss, the carcinoma is suspected, although similar clinical symptoms may be recognized in chronic otitis media as well. In addition, the characteristic signs and symptoms of carcinoma are also the following: changes in temporomandibular joint, parotid gland swelling, painless solitary mastoid swelling, neurological disorders, sudden occurrence of polyps and granulation tissue (recurrent polyps and granulation tissues after the removal), signs and symptoms of otogenic complications, as well as generalized weakness, weight loss and other biological disturbances. The diagnostic approach may include generally accepted recommendations and treatment protocols.
Keywords: carcinoma of the middle ear; clinical picture; diagnosis